Google Earth Forensics Using Google Earth Geo-Location in Digital Forensic Investigations - Harrington, Michael (Elsevier Science, 2014)
Google Earth Forensics is the first book to explain how to use Google Earth in digital forensic investigations. This book teaches you how to leverage Google's free tool to craft compelling location-based evidence for use in investigations and in the courtroom. It shows how to extract location-based data that can be used to display evidence in compelling audiovisual manners that explain and inform the data in contextual, meaningful, and easy-to-understand ways. As mobile computing devices become more and more prevalent and powerful, they are becoming more and more useful in the field of law enforcement investigations and forensics. Of all the widely used mobile applications, none have more potential for helping solve crimes than those with geo-location tools. Written for investigators and forensic practitioners, Google Earth Forensics is written by an investigator and trainer with more than 13 years of experience in law enforcement who will show you how to use this valuable tool anywhere at the crime scene, in the lab, or in the courtroom. Learn how to extract location-based evidence using the Google Earth program or app on computers and mobile devicesCovers the basics of GPS systems, the usage of Google Earth, and helps sort through data imported from external evidence sourcesIncludes tips on presenting evidence in compelling, easy-to-understand formats